Peningkatan Keterampilan Penggunaan Learning Management System Menggunakan Moodle Gnomio untuk Tenaga Pengajar di Lembaga Pendidikan Permata Bunda - Ahmad Swandi; Sri Rahmadhanningsih; Susalti Nur Arsyad; Asdar Asdar (Tongkonan: Jurnal Pengabdian Masyarakat, 2022)
Digital competence of teachers is needed to be able to be creative in the implementation of online learning through the use of various ICT products. One of the problems experienced by teachers and community members from the Permata Bunda Educational Institution (LPPB) is the lack of knowledge and experience in using e-learning or the Learning Management System (LMS). Therefore, training and mentoring are carried out which aim to encourage teachers and community members to be able to create e-learning-based learning media. The e-learning development training activity was carried out for one day followed by mentoring activities. This activity was carried out in collaboration with a team of lecturers from the Faculty of Teacher Training and Education at the University of Bosowa with the Permata Bunda Educational Institution through the Matching Fund Kedaireka 2021 program. The training was carried out in a hybrid manner where community members from LPPB were present directly in the activity, while participants from other agencies followed online using an application. zoom. The training was carried out for one day by dividing into 3 types of activities, namely the introduction of the Learning Management System (LMS), direct practice of making LMS Moodle and evaluation of activities. As an evaluation material, at the end of the activity, participants filled out a satisfaction questionnaire with the ongoing training activities. Based on the results of the analysis, the majority of participants' mastery of the training material was in the good category. Meanwhile, the participants' ability to follow instructions from the resource persons was also in the good category.